Controle ativo de vibrações em rotor flexível utilizando compensação distribuída paralela - Corrêa, Renan Franco (2017)
The current work uses the electromagnetic actuator to perform the active vibration control of a flexible rotor. This actuator uses electromagnetic forces to control the rotor without mechanical contact. The electromagnetic actuator exhibit a non-linear behavior, therefore linear control techniques cannot be directly applied, which justifies the control by Fuzzy Logic. In this work, the aim is to attenuate rotor system vibration by parallel distributed compensation based on Takagi-Sugeno local models, in order to achieve a non-linear global controller. Simulation results demonstrate the efficiency of this approach, given that there is a reduction in the vibration amplitude in the analyzed cases.